Oxford American Handbook of Clinical Examination and Practical Skills - Burns, E. A. Elizabeth A (Worldwide best-seller, 2011)
The Oxford American Handbook of Clinical Examination and Practical Skills is a comprehensive pocket guide for medical, physician assistant, and nurse practitioner students. It is designed to help students transition from classroom to clinical internships, preceptorships, and clerkships. Providing clear and user-friendly guidance on all aspects of history taking, physical examination, common practical procedures, data interpretation and communication skills, it gives realistic advice on coping with and mastering common situations. Each systems chapter follows a structured format covering applied anatomy, history, examination, and the presentation of common and important disorders. The procedures section includes approximately forty practical procedures that the final year medical student and senior nurse are expected to perform. The section on data interpretation covers the basics of chest x-rays, abdominal x-rays, ECGs, lung function tests and several other areas that the student is expected to carry out in their early years of training.